(3JdNjU cJGH GdMejGJ dLGdjfhSs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3GHQGgje Hf CMeO Hf SdjeGf HLjQ GdCROi s)
(3ChdgG (B:s
(3eHJhQ GdChd, hChd GdehLhO efg(B: ((3cdeG(B) (3cGf CTO hCbhi cGf GdGfUHGH , hcdeG cGf CVYa cGf Cbd s
(3BNQgG (B:s
(3cja JbJd HYV GdMejGJ ai GdGHJOGA HEfWaGA GdMQGQI GdZQjRjI ai LejY LhgQgG Edi GdMQGQI GdZQjHI EeG GdeMQbI hEeG GdeHQOI GdNGfbI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B69 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdWHs